The ‘Rocket Framework’: A Novel Framework to Define Key Performance Indicators for Nature-based Solutions Against Shallow Landslides and Erosion - Gonzalez-Ollauri, Alejandro; Munro, Karen; Mickovski, Slobodan B.; Thomson, Craig S.; Emmanuel, Rohinton (Frontiers in Earth Science, 2021)
The idea of nature providing solutions to societal challenges is relatively easy to understand by the layperson. Nature-based solutions (NBS) against landslides and erosion mostly comprise plant-based interventions in which the reinforcement of slopes provided by vegetation plays a crucial role in natural hazard prevention and mitigation, and in the provision of multiple socio-ecological benefits. However, the full potential of NBS against landslides and erosion is not realised yet because a strong evidence base on their multi-functional performance is lacking, hindering the operational rigour of NBS practice and science. This knowledge gap can be addressed through the definition of repositories of key performance indicators (KPIs) and metrics, which should stem from holistic frameworks facilitating the multi-functional assessment of NBS. Herein, we propose the ‘rocket framework’ to promote the uptake of NBS against landslides and erosion through the provision of a comprehensive set of indicators which, through their appropriate selection and measurement, can contribute to build a robust evidence base on NBS performance. The 'rocket framework’ is holistic, reproducible, dynamic, versatile, and flexible in helping define metrics for NBS actions against landslides and erosion along the NBS project timeline. The framework, resultant from an iterative research approach applied in a real-world environment, follows a hierarchical approach to deal with multiple scales and environmental contexts, and to integrate environmental, eco-engineering, and socio-ecological domains, thus establishing a balance between monitoring the engineering performance of NBS actions against landslides and erosion, and the wider provision of ecosystem functions and services. Using a case study, and following the principles of credibility, salience, legitimacy, and feasibility, we illustrate herein how the 'rocket framework’ can be effectively employed to define a repository with over 40 performance indicators for monitoring NBS against landslides and erosion, and with over 60 metrics for establishing the context and baseline upon which the NBS are built and encourage their reproduction and upscaling.